Applied Value at Risk in the South East Asia Stock Market, Does it Work? - Hendrawan, Riko (Santoso Academy Network, 2026)
This study uses historical data to calculate VaR, a widely accepted approach due to its simplicity and empirical basis (Olson & Wu, 2017), in the Southeast Asian stock market. The results show that the index with the highest VaR value at the 1% confidence level is the Hanoi Stock Exchange Index from Vietnam. High VaR values ​​in these indices reflect the potential for significant losses in a worst-case scenario. The study also shows that the VaR value increases with the confidence level. This means that, at a higher confidence level, for example, 1%, the VaR value will be greater than at 5% or 10%. A higher confidence level reflects a desire to account for more extreme and rare scenarios. By considering the study period, which includes financial crises such as the 2008 crisis and the COVID-19 pandemic, this study provides relevant insights for investors on the dynamics of risk and return in Southeast Asian stock markets. This study emphasizes the importance of using VaR as a risk management tool to help investors make more informed, prudent investment decisions.